ALTERNATIVE APPROACH TO THE PROFESSIONALISM IN CIVIL SERVANT: A LITERATURE REVIEW - Aditya Widya Septian (Jurnal Indonesia Sosial Sains, 2021)
The article's motive is to compile professionalism from various fields and offers a framework related to professionalism in the public sector. Therefore, not many academics have primarily discussed professionalism in the public sector regarding the component that establishes professionalism and its implication on organizational processes. Furthermore, the demands from the society also make public organizations make a paradigm shift towards NPM (new public management). The NPM urges the change to the organizational process for implementing competence and performance to its human resource. Thus, the human resource in the public sector needs to transform to be a professional to overcome the challenges and the complexity of public demands in the future. This article uses qualitative methods with a literature review and comparison approach to the model professionalism that has already been developed by the academic. The conclusion showed that the concept of professionalism is a function formed by five interrelated factors and can integrate with performance and competence.